ANALISIS PEMASARAN KOPI DI KABUPATEN HUMBANG HASUNDUTAN PROVINSI SUMATERA UTARA - Erwin Nasution; Syahbudin Syahbudin (Universitas Medan Area, 2018)
This study aims to determine the types of marketing channels, marketing functions in each channel marketing, marketing costs, share margins and price spread on each channel as well as the level of efficiency in the coffee marketing District Humbang Hasundutan. This study was carried on in the district as one of Humbang Hasundutan coffee production center in North Sumatra. The set of ten districts in three districts namely purporsif Lintong Nihuta districts, and a bun Dolok Sanggul, Paranginan as coffee producing districts in the District Humbang Hasundutan. This study uses field observation questionnaire and interviews, from three districts defined population of 93 coffee farmers randomly selected, 63 village traders, merchants 15 district level, district 6 merchants and traders 5 provinces (exporters). The model used data analysis is descriptive and quantitative analysis. The results showed that there are four (4) copies of marketing channels District Humbang Hasundutan, Channel Marketing I : Farmers - Traders Village - District of Traders - Traders District - Traders Province/exporters, Channel Marketing II : Farmers - District of Traders - Traders district - Traders Province/ exporters, Marketing Channels III : Farmers - Merchant District - Traders Province/exporters, Marketing Channels IV : Farmers - Merchants Province/ exporters. Each institution plays the marketing of at least 4 functions, from the existing 4 channel 3 channel turns out to have a good level of efficiency compared to most other 3 channels because of the small value of marketing efficiency. Keywords : Coffee Marketing, Channel Marketing, Marketing Costs, Marketing Margins, Price Spread and Marketing Efficiency.